2003
DOI: 10.1890/0012-9658(2003)084[0736:lthova]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term History of Vegetation and Fire in Pitch Pine–oak Forests on Cape Cod, Massachusetts

Abstract: Abstract. Human disturbance in northeastern North America over the past four centuries has led to dramatic change in vegetation composition and ecosystem processes, obscuring the influence of climate and edaphic factors on vegetation patterns. We use a paleoecological approach on Cape Cod, Massachusetts, to assess landscape-scale variation in pitch pine-oak vegetation and fire occurrence on the pre-European landscape and to determine changes resulting from European land use. Fossil pollen and charcoal preserve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(85 citation statements)
references
References 50 publications
(43 reference statements)
1
84
0
Order By: Relevance
“…Perhaps, then, the expansive marshland observed today is a metastable, relict feature that developed under higher sediment supply rates in the past. For example, sedimentation rates in the Chesapeake Bay and Coastal Massachusetts increased 4 to 10 times after European settlement and deforestation (29,30), and marshes of the Plum Island Estuary in Massachusetts were likely restricted to the fringes of an open-water basin until some time after 680 years B.P. (31).…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps, then, the expansive marshland observed today is a metastable, relict feature that developed under higher sediment supply rates in the past. For example, sedimentation rates in the Chesapeake Bay and Coastal Massachusetts increased 4 to 10 times after European settlement and deforestation (29,30), and marshes of the Plum Island Estuary in Massachusetts were likely restricted to the fringes of an open-water basin until some time after 680 years B.P. (31).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, our ability to properly assess the veracity of the results of our pre-colonial scenarios is limited due to a lack of objective data sources for the study area. In other areas of New England and the Mid-Atlantic, colonial era land surveys (e.g., Cogbill et al, 2002;Russell, 1981) and palynological studies (Watts, 1979;Russell and Standford, 2000;Russell and Davis, 2001;Parshall et al, 2003) have been used to reconstruct pre-colonial era vegetation regimes. However, the colonial era land survey record for the area of the NJPB has not been carefully investigated and it is unclear whether they will provide sufficient information to resolve the vegetation patterns of the pre-colonial era.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of these forest types reflects regional climatic conditions: boreal conifers are currently widespread at higher elevations and in northern regions of New England, northern deciduous hardwoods are mainly distributed in the cooler central uplands, and mixed oak-hickory forests are found at lower elevations and more southerly regions. Although the current relationship between climate and New England forests is partly obscured by human activities and ecological succession following land abandonment (e.g., Parshall et al 2003), historical evidence (e.g., Shuman et al 2004) has demonstrated a strong relationship between climate and forest dynamic in New England. To evaluate the effects of historical climate variation on forest NPP and biomass in the study region, we excluded all land-cover types that are currently subject to substantial human use.…”
Section: The Study Regionmentioning
confidence: 99%